Contemporary Rhetorical Citizenship - Villadsen, Lisa S., 1968-; Kock, Christian (Book collections on Project MUSE., 2014)
This book offers the concept of rhetorical citizenship as a meeting ground for the burgeoning community of scholars interested in rhetoric's place in society. It brings together contributions from several disciplinary traditions in communication studies and neighbouring fields. The concept of rhetorical citizenship highlights the discursive, processual, and participatory aspects of civic life. It builds on the ancient idea that rhetoric is what makes civilized society possible; citizenship is in large part discursively based. Legal rights, privileges and material conditions are not the only constituents of citizenship; discourse between citizens is arguably the basis of what it means to be a citizen.0.